Motivasi dan Swadaya Masyarakat Penerima Bantuan Stimulan Perumahan Swadaya - Asminar, Asminar (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
The recipient of a self-help housing stimulus program (BSPS) must meet the conditions set by the Ministry of Public Works and Public Housing, namely Indonesian citizens who have a family, own or control land, do not have a house or own and occupy the only house with conditions unfit for habitation, have never received stimulant assistance from self-help housing from the central government, earning the most worth the local provincial minimum wage, and most preferably people who want to support themselves until the house is built into a habitable house. The purpose of this service is to find out the motivation and self-reliance of the community in making a decent house in the village of Tirta kencana, Rimbo Bujang Subdistrict, Tebo.The activity is carried out on stairs 17 April to 30 July 2019. Community service methods carried out are counseling, surveying, monitoring and evaluation. The data obtained from this service were analyzed in a description of 2 groups of beneficiaries in the village of Tirta Kencana, consisting of 15 groups of people, so all of them were 30 people. The data used is primary data and secondary data. The results of the study showed that the motivation of the community to take part in the self-help housing (BSPS) stimulant assistance program was that there were many community members so that they could make a decent house with only Rp. 17,500,000, the size of a house that makes up a majority of more than 6X6 M.